IMPLEMENTASI MODEL PBL BERBASIS LINGKUNGAN SEKOLAH DI SD PAJAGALAN I SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS VI PADA PEMBELAJARAN BAHASA INDONESIA - Masitoh Bunga Ayu Seruni; Sama’; Muhammad Misbahuddholam AR (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Indonesian language learning is very important to be mastered by students. The success of this learning can be seen from the learning outcomes obtained by students. However, there are still many problems with learning outcomes in Indonesian language lessons. The purpose of this study is to analyze in depth the implementation of the Problem-Based Learning (PBL) model at SD Pajagalan I as a strategic effort to improve student learning outcomes in Indonesian language subjects. This study uses a descriptive qualitative research method. The subjects in this study were the homeroom teachers of grade VI of SD Pajagalan I, using interview techniques and literature studies. Data analysis techniques use the Miles & Hubeirman modeil which includeis threiei main stageis, nameily data reiduction, data preiseintation and drawing conclusions. Thei reisults of thei study obtaineid thei impleimeintation of PBL baseid on thei school einvironmeint at SD Pajagalan 1 was carrieid out through thei planning, impleimeintation, and eivaluation proceisseis. Thei planning carrieid out was in thei form of preiparing to choosei probleims that weirei in accordancei with thei mateirial, PBL impleimeintation was carrieid out through PBL syntax, and eivaluation of thei PBL modeil baseid on thei school einvironmeint obtaineid that this modeil could improvei studeint leiarning outcomeis. Thus, this study provideis reicommeindations for schools to bei ablei to impleimeint PBL leiarning baseid on thei school einvironmeint to oveircomei probleims of studeint leiarning outcomeis.